2020
DOI: 10.1093/europace/euaa313
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of left atrial fibrosis detection with cardiac magnetic resonance: correlation of late gadolinium enhancement with endocardial voltage and conduction velocity

Abstract: Aims Myocardial fibrosis is a hallmark of atrial fibrillation (AF) and its characterization could be used to guide ablation procedures. Late gadolinium enhanced-magnetic resonance imaging (LGE-MRI) detects areas of atrial fibrosis. However, its accuracy remains controversial. We aimed to analyse the accuracy of LGE-MRI to identify left atrial (LA) arrhythmogenic substrate by analysing voltage and conduction velocity at the areas of LGE. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 19 publications
1
43
0
Order By: Relevance
“…The authors speculated that far‐field potentials might conceal small local electrograms. Therefore, atrial fibrosis might remain undetected by conventional electroanatomical mapping, and LGE‐MRI might be a more sensitive technique than SR bipolar voltage to characterize atrial fibrosis 19 . Although the data were not shown, the distribution of the low‐voltage area, defined as an atrial voltage less than 0.5 mV, in the SR was not completely consistent with that of the LGE.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The authors speculated that far‐field potentials might conceal small local electrograms. Therefore, atrial fibrosis might remain undetected by conventional electroanatomical mapping, and LGE‐MRI might be a more sensitive technique than SR bipolar voltage to characterize atrial fibrosis 19 . Although the data were not shown, the distribution of the low‐voltage area, defined as an atrial voltage less than 0.5 mV, in the SR was not completely consistent with that of the LGE.…”
Section: Discussionmentioning
confidence: 90%
“…The accuracy of the voltage mapping during SR was limited after multiple DC shocks in the non‐PAF patients. Caixal et al 19 demonstrated that LGE intensity was associated with log‐transformed bipolar voltage and conduction velocity in SR. The authors speculated that far‐field potentials might conceal small local electrograms.…”
Section: Discussionmentioning
confidence: 99%
“…High intensity areas on late Gadolinium enhancement magnetic resonance images (LGE-MRI) as well as low bi- and unipolar electrogram voltages [ 7 , 8 , 9 ] during electrophysiological studies are currently drawn on to identify the amount and spatial location of scars and fibrosis on the atrial wall. However, LGE-MRI is a cost-intensive imaging technique for which technical parameters have to be carefully selected and the segmentation of MR images is cumbersome and challenging [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Substrate ablation strategies guided by a voltage map derived from the amplitude of intracardiac electrograms define areas based on a cut-off value (frequently < 0.5 mV during sinus rhythm) as pathological tissue and target them for ablation [4][5][6] . Several clinical studies have shown a correlation of fibrosis identified through late gadolinium enhancement magnetic resonance imaging (LGE-MRI) with reduced local signal amplitude ("voltage") in atrial electrograms 7,8 . Using low voltage areas as targets for ablation has not yet shown an optimal and consistent reduction in the rate of recurrent atrial fibrillation [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%